Effects of Baduanjin exercise on motor function, balance and gait in Parkinson’s disease: a systematic review and meta-analysis - Ying Chen; Xi Cheng; Min Xia; Liyan Yang; Jinghui Lai; Yangfan Cai (BMJ Open, 2022)
Objective This study aims to systematically evaluate the effects of Baduanjin on motor function, balance and gait in patients with Parkinson’s disease (PD).Design Systematic review and meta-analysis.Study selection All eligible randomised controlled trials (RCTs) published in the English and Chinese language were included.Data sources Ten electronic databases were systematically searched, from inception to 17 March 2022: PubMed, Web of Science, Cochrane Library, Embase, EBSCOhost, OVID, SinoMed, China National Knowledge Infrastructure, Wanfang Data and China Science Journal Database (VIP).Review methods Methodological quality assessment and meta-analysis were performed for the included studies using the Cochrane Review Manager V.5.4 software.Results Ten RCTs with 804 participants were included. The results revealed the following: (1) Baduanjin significantly improved the motor function of patients with PD, based on the Unified Parkinson’s Disease Rating Scale Part III (mean difference, MD −5.37, 95% CI −8.96 to −1.78, p=0.003) and Fugl-Meyer Assessment of Lower Extremity (MD 5.39, 95% CI 2.71 to 8.07, p<0.0001); (2) Baduanjin significantly improved the ability of balance of patients with PD, based on the Berg Balance Scale (MD 4.40, 95% CI 3.08 to 5.73, p<0.00001); (3) Baduanjin significantly improved the gait of patients with PD, based on the 6 min walk distance (MD 21.62, 95% CI 11.14 to 32.10, p<0.0001). After the further subgroup and sensitivity analyses, the heterogeneity was identified to be potentially due to the different degrees of disease severity in patients with PD and the difference in Baduanjin intervention durations.Conclusions The analysis of this systematic evaluation indicates that Baduanjin might have a positive effect in improving the motor function, balance and gait of patients with PD. However, due to the quantity and clinical heterogeneity limitations of the included studies, this conclusion still warrants more high-quality and multicentre RCTs for further verification.